Front Cover: Protamine Promotes Direct Electron Transfer Between Shewanella oneidensis Cells and Carbon Nanomaterials in Bacterial Biocomposites (ChemElectroChem 9/2019). Issue 9 (23rd April 2019) - Pinck, Stéphane; Jorand, Frédéric P. A.; Xu, Mengjie; Etienne, Mathieu
Abstract : The Front Cover shows the building block of the bacterial biocomposite made of Shewanella oneidensis, multi‐walled carbon nanotubes, and protamine. The close look at the bacterial membrane shows how protamine, which is positively charged (in blue), promotes self‐assembly between the negatively charged polymers on the bacterial membrane surface (in red) and the negative surface of multi‐walled carbon nanotubes, allowing direct electron transfer reactions. The background of the image is a detail of a scanning electron microscopy image of the biocomposite deposited on a glassy carbon surface, forming the so‐called electroactive artificial biofilm. More information can be found in the Article by S. Pinck et al. onpage 2398 in Issue 9, 2019 (DOI:10.1002/celc.201801751 ).